Benchmarking the Energy Efficiency of Higher Educational Buildings: A Case Study Approach - Mohd Shukri, Muhammad Azim; Jailani, Junaidah; Hauashdh, Ali (International Journal of Energy Economics and Policy, 2022)
Previous studies have reported that buildings consume nearly 36% of the total energy used and contribute towards 30% of the total carbon dioxide (CO2) emissions. Therefore, improving energy efficiency in buildings is essential to enhance a sustainable built environment. This research employed a case study approach with the Universiti Tun Hussein Onn Malaysia (UTHM) being selected as the case study. A number of buildings recorded high annual energy consumption (EC) data while others recorded low energy consumption. This was due to the absence of a benchmark line reference for campus buildings, thereby causing a significant difference in the energy consumption of each building. The study’s aim was to develop an energy efficiency benchmark for university buildings by using statistical analysis. From statistical analysis, the standard practical range was between 72.5–141.0 kWh/m2/yr. Buildings with an energy consumption per unit area value below 72.5 kWh/m2/yr are regarded as best energy efficient buildings. In contrast, those above 141.0 kWh/m2/yr are considered poor energy efficient buildings. For recommendation, buildings that exceed the maximum value of this range require stricter supervision and monitoring by the university management.